HAK CIPTA SEBAGAI OBYEK JAMINAN FIDUSIA DITINJAU DARI UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA DAN UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - Merista, Ovia (Faculty of Law, Parahyangan Catholic University, 2016)
This article shall discuss the possibility to utilize copyright as fiduciary security to a loan, in accordance to Law No. 42 of 1999 regarding fiduciary pledge/security and the Copyrights Law (Law No. 28 of 2014). The use of copyrights as a fiduciary security is made possible as copyright owner possess exclusive economic rights and not only moral rights. The procedure to be followed is regulated by Law No. 42 of 1999. The economic value of the copyright, is however, determined by the (potential) utilization of the object. In fact the value is calculated against the copyright holder’s right to remuneration or royalty. Keywords: copyrights, security to a loan, fiduciary, moral and economic exclusive rights